Optimization, Purification, Kinetic analysis and Applications of alkaline proteases produced from Bacillus subtilis utilizing agricultural by products through solid state fermentation: DOI: 10.48129/kjs.12103 - Abullah, roheena; Asim, Maham; Nadeem, Muhmmad; Nisar, Kinza; Kaleem, Afshan; Iqtedar, Mehwish (Kuwait Journal of Science, 2022)
Proteases have gained more commercial value to date due to multiple applications in different industrial sectors. Current research was intended to use the cheaper agricultural waste for maximal protease production. Optimal conditions for the production of protease by solid-state fermentation was achieved at 37 °C, incubation period of 24 h, pH 9.0, inoculum size 3%, 1.5 g sucrose as carbon source and 30% moisture content. Among the various inorganic and organic nitrogen sources, ammonium nitrate 5g, yeast extract 2 g tremendously increased the production of protease. Among metal ions and surfactants tested, Ca2+ and Tween 40 showed the optimal protease production. The purification of protease was carried out by ammonium salt precipitation followed by sephadex G-100 gel filteration chromatography. The 1.3 fold purification with 37.5 % yield purification along with 51.5 U/mg of specific activity was obtained. Molecular weight of purified protease was confirmed with a single band of 36.12 kDa. The protease was quite stable over a temperature range of 35-45 °C and pH 7-9, with maximal activity at 40 °C and pH 9. The kinetic parameters Vmax (maximum rate) and Km (Michaelis-Menten constant) were calculated as 0.307 U/g and 11.2 mg/mL, respectively. The application of alkaline protease indicates it effectively de-haired goat skin and successfully removed the animal blood stain from cotton cloth.